THE FINANCIAL MANAGEMENT PRACTICE OF MOSQUE: STUDY CASE IN MALAYSIA - Islamiyah, Nining (Jurnal Akuntansi dan Keuangan Indonesia, 2019)
This study aims to explain the financial management practices of the mosque. Specifically, the focus of this study is to explore and investigate how financial management practices in the mosque. A case study of one Malaysian mosque is undertaken. To achieve the objective of this study, the researcher used various techniques of data collection, including interviews, observations, and reviews of the documents. The findings reveal that the SHAS mosque has four mechanisms to manage financial management practices. The tools are performance assessment and evaluation, participation, regulation, and social auditing. This study concludes that financial management practices are a necessary process to support the accountability of the mosque. Especially, secondary accountability relates to the responsibility of mosque managers toward capital providers of the mosque. The results of this study give some implications for the improvement of financial management practices, particularly in the mosque.